SOSIALISAI UNDANG – UNDANG ITE CERDAS DI DUNIA NYATA, BIJAK DI DUNIA MAYA BERSAMA GERAKAN PRAMUKA SMK MA’ARIF BANYUMAS - Adi Prasetya Nanda; Ida Ayu Putu Anggie Sintiya (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Advances in communication and information technology deserve recognition. Sophistication is increasingly dominating the ladder of life which begins to move to an area without borders. Every progress does have positive and negative effects. We just need to be aware of and avoid negative effects. The rise of crimes in cyberspace, such as the spread of viruses, fake news, violence, fraud, data theft, the distribution of personal photos / videos, pornography and so on, is clear evidence that the use of the internet must have sufficient knowledge about the dangers and anticipation. Based on the contents of Article 28 paragraph 1 in the ITE Law, spreading false information aka hoaxes can be subject to heavy sanctions. Anyone who knowingly and or without the right spreads false and misleading news, the threat can be subject to a maximum sentence of six years and a maximum fine of Rp 1 billion. Problems that often occur among the community or adolescents in using social media, especially students in vocational high schools (SMK), are lack of understanding of how to literate news on social media so that sometimes students easily believe news that is not certain the truth.